Internet marketing and its impact on the development of handicraft export (case study: Isfahan Province) - Gholami Samira (2023)
The development of Internet technology has had a vast impact on business processes, so it is a suitable platform for the activities of most companies. Today, exports are carried out internationally. Many organizations are aware of the elements of internet marketing. Since the handicraft industry of Iran and Asia has a long history, Internet marketing and the Internet provides an excellent opportunity to develop its exports. This research examines the elements of Internet marketing and its relationship with the export performance of handicrafts. The city of Isfahan in Iran is efficient in various fields of this industry. This research data was designed using a questionnaire consisting of 23 questions. Cronbach’s alpha coefficient is 0.94, and experts have confirmed its validity. SPSS software, inferential statistics, and Pearson correlation test were used to check research hypotheses. More complete analyzes of regression analysis have been used. The independent variable of this research is marketing mix elements, including promotion, transaction, exchange, and supply. The dependent variable of export performance has been examined in two dimensions, financial and strategic. After reviewing a central hypothesis and eight sub-hypotheses, there is a positive relationship between the Internet marketing elements related to advertising, exchange, exchange, and supply and the export performance of the investigated companies. Finally, the effectiveness of each of these elements was checked using regression analysis, and the ranking and importance of each parameter were introduced. The exchange had the most significant impact on internet marketing.